2014
DOI: 10.1128/genomea.00740-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Propionibacterium acnes Type Strain ATCC6919 and Antibiotic-Resistant Strain HL411PA1

Abstract: Propionibacterium acnes is a major skin commensal and is associated with acne vulgaris, the most common skin disease. Here we report the draft genome sequences of two P. acnes strains, the type strain ATCC6919 and an antibiotic-resistant strain, HL411PA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…A PCR product spanning the two ends with the predicted size (~735 bp) and sequence was amplified from all the phages tested, suggesting that the phage DNA can exist in a circular form mediated by the overhangs at the ends (Supplementary Figure S6A). To demonstrate the pseudolysogenic properties of P. acnes phages, we infected P. acnes strain ATCC6919, a clade IA-1 strain (Liu et al, 2014), with five different phages (PHL060L00, PHL112N00, PHL037M02, PHL073M02 and PHL114L00). Following the formation of plaques by each phage, regrowth of the bacteria was observed starting in the center of the plaque regions.…”
Section: Diversity Of P Acnes Phages In the Human Skinmentioning
confidence: 99%
“…A PCR product spanning the two ends with the predicted size (~735 bp) and sequence was amplified from all the phages tested, suggesting that the phage DNA can exist in a circular form mediated by the overhangs at the ends (Supplementary Figure S6A). To demonstrate the pseudolysogenic properties of P. acnes phages, we infected P. acnes strain ATCC6919, a clade IA-1 strain (Liu et al, 2014), with five different phages (PHL060L00, PHL112N00, PHL037M02, PHL073M02 and PHL114L00). Following the formation of plaques by each phage, regrowth of the bacteria was observed starting in the center of the plaque regions.…”
Section: Diversity Of P Acnes Phages In the Human Skinmentioning
confidence: 99%
“…Certain subtypes may be better adapted at thriving in the deep tissues and causing clinical infection than others (13,14,16). Also, some subtypes may be more strongly associated with clinical markers of infection, such as hemolysis, and antibiotic resistance (16)(17)(18)(19)(20)(21)(22). Sequencing of deep tissue samples has recently become a candidate for potential rapid diagnosis (23) and for identifying virulent and antibiotic-resistant strains (14).…”
mentioning
confidence: 99%
“…Cationic AMPs, like P5, show broad-spectrum antimicrobial activity, kill target cells rapidly, and are active against antibiotic resistant and clinically relevant pathogens, including P . acnes [ 3 , 29 , 30 ]. It is generally accepted that the mechanism of action of cationic AMPs involves their direct interaction with the negatively charged bacterial membranes, which causes an increase in membrane permeability that rapidly leads to cell death [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…acnes directly stimulate the production of TNF-α and IL-8 via TLR expression [ 37 ]. Recent studies have shown that cationic peptides can inhibit the inflammation induced by bacteria, perhaps by altering cytokine production [ 30 32 ]. For example, several synthetic cationic AMPs have been shown to block LPS- and LTA-stimulated production of pro-inflammatory cytokines by macrophages [ 29 ].…”
Section: Discussionmentioning
confidence: 99%